CD14+ monocytes: the immune communication hub in early vasculitis symptoms of Kawasaki disease - Song, Sirui; Chen, Liqin; Zhou, Yuanyuan; Xu, Yanbing; Li, Guang; Shen, Libing; Xiao, Tingting; Huang, Min (Frontiers in Immunology, 2025)
BackgroundKawasaki Disease (KD) is an acute systemic vasculitis syndrome predominantly affecting children, with a propensity to induce coronary artery lesions. Aberrant immune activation and cytokines cascade reactions are involved in its pathogenesis. The aim of this study is to investigate the changes in immune cell communication during the course of KD and to identify potential biomarkers.MethodsThe study enrolled seven pediatric patients diagnosed with Kawasaki Disease (KD) between December 2019 and December 2021. Single-cell RNA sequencing (scRNA-seq) technology was utilized to analyze peripheral blood mononuclear cells (PBMCs). Bioinformatics methods including quality control, dimensionality reduction, cell annotation, differential expression analysis, cell communication analysis, and co-expression network analysis were employed for data processing and analysis.ResultsThis study utilized single-cell sequencing technology to uncover the dynamics of immune cell communication during the course of KD, revealing a significant increase in the number of CD14+ monocytes in the early stages of vasculitis, which play a central role in cell-cell communication. SELPLG was identified as a particularly crucial gene in the signal transduction among immune cells. The study also observed various cellular communication patterns of vasculitis at different time points and identified co-expression modules related to ribosomal function, cell proliferation, and immune responses in CD19+ B cells, CD4+ T cells, CD8+ T cells, CD14+ monocytes, and CD16+ monocytes. Notably, the expression of the ITK gene in CD14+ monocytes stood out. Furthermore, MHC-I genes were the most active molecules involved in signal transduction, and the expression of CD40 genes increased with the prolongation of vasculitis duration.ConclusionCD14+ monocytes play a pivotal role in cellular communication during the activation process of KD vasculitis, with SELPLG and ITK as important communication signal genes. These findings provide a novel perspective for the discovery of biomarkers, prediction of disease progression, and the development of targeted treatment strategies for KD.Clinical Trial Registrationhttp://www.medresman.org.cn/pub/cn/proj/projectshow.aspx?proj=7739, identifier ChiCTR, ChiCTR2100044729.